If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + -6(4 + 5x) = -6 5x + (4 * -6 + 5x * -6) = -6 5x + (-24 + -30x) = -6 Reorder the terms: -24 + 5x + -30x = -6 Combine like terms: 5x + -30x = -25x -24 + -25x = -6 Solving -24 + -25x = -6 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '24' to each side of the equation. -24 + 24 + -25x = -6 + 24 Combine like terms: -24 + 24 = 0 0 + -25x = -6 + 24 -25x = -6 + 24 Combine like terms: -6 + 24 = 18 -25x = 18 Divide each side by '-25'. x = -0.72 Simplifying x = -0.72
| x^3-18x^2+17x=0 | | 5-9x=49-37x | | x(x+7)=x^2 | | 54-7x=2x+24 | | 2x+12x-14-108=24x+30 | | -6(-4)(-7)= | | 7-10x=67-45x | | Q=3000-10p | | 5x+2x=2x-4 | | -x^2+5x+14=0 | | 18-2x=6-10x | | 8n+3=67 | | 8x-17=5x+11 | | -2(6)(1)(-4)= | | 71-6x=8+15 | | 2x+6=-24 | | 4-3x=7x+1 | | 10x-118=6x-14 | | (n-4)*7=56 | | (n-7)*2=8 | | -2(n-1)-4n= | | 105-3x=33x+17 | | 7-10x=20-17x | | 2x+31=9x-32 | | 3x+7=-113-9x | | 12x-3=10+5 | | 141-6x=4x+11 | | 2x+12x-14-12=24x+30 | | 137-6x=6x+5 | | 5x+24=13x-72 | | 5y-20=(3x*4)+5 | | 5x+5=85-5 |